2003
DOI: 10.1179/096805103225001468
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic receptor regulation of LPS-induced signaling and pathophysiology

Abstract: Macrophages express several lipopolysaccharide (LPS) binding proteins and are potently activated by LPS to produce inflammatory mediators. Recent studies have shown that receptors for exogenous nucleotides (P2X and P2Y purinergic receptors) can modulate macrophage production of TNF-alpha, IL-1beta and nitric oxide (NO) following LPS exposure. Macrophages and LPS-stimulated monocytes express elevated levels of P2Y1, P2Y2 and P2X7 mRNA, suggesting that both P2Y and P2X receptors can contribute to LPS-induced pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 3 publications
1
31
0
Order By: Relevance
“…P2Y 2 , P2Y 4 and P2Y 6 receptors are also expressed by macrophages. The P2Y 2 subtype was found to promote transcription of IL-6 [177] and the coordinate action of P2Y and P2X receptors modulated LPS-induced TNF-α-, IL1-β-and NO-production [178]. In murine J774 macrophages LPS-induced COX2 upregulation and subsequent PGE 2 -stimulated iNOS induction was potentiated by UTP acting at the P2Y 6 receptor.…”
Section: Inflammation Allergies and Host Defencementioning
confidence: 98%
“…P2Y 2 , P2Y 4 and P2Y 6 receptors are also expressed by macrophages. The P2Y 2 subtype was found to promote transcription of IL-6 [177] and the coordinate action of P2Y and P2X receptors modulated LPS-induced TNF-α-, IL1-β-and NO-production [178]. In murine J774 macrophages LPS-induced COX2 upregulation and subsequent PGE 2 -stimulated iNOS induction was potentiated by UTP acting at the P2Y 6 receptor.…”
Section: Inflammation Allergies and Host Defencementioning
confidence: 98%
“…For example, it has been observed that LPS-induced IL-1␤ release from peritoneal macrophages isolated from P2RX7 Ϫ/Ϫ mice is compromised when compared with that observed with wild-type control littermates [5]. Moreover, murine RAW 264.7 macrophages that express a nonactive form of P2RX7 have reduced LPS-induced NO release as compared with macrophages with functional P2RX7 [6]. In terms of other diseases, P2RX7 Ϫ/Ϫ mice also exhibit a reduced incidence and severity of anti-collagen-induced arthritis symptoms when compared with their littermate (P2RX7 ϩ/ϩ ) controls [7].…”
Section: Introductionmentioning
confidence: 99%
“…The use of AMPs is one potentially effective approach to the treatment of MDR A. baumannii. AMPs are particularly attractive as new antimicrobial agents against MDR bacteria, including A. baumannii, because their mechanism of action, which involves permeation of the bacterial membranes, reduces the likelihood of emergence of resistance (40)(41)(42)(43)(44)(45). That said, other bacteria do exhibit mechanisms to resist AMPs (46)(47)(48).…”
Section: Effects Of Antibiotic Agents On Mdr a Baumannii Cells The 19mentioning
confidence: 99%